2022
DOI: 10.3390/molecules27092838
|View full text |Cite
|
Sign up to set email alerts
|

Covalently Immobilizable Tris(Pyridino)-Crown Ether for Separation of Amines Based on Their Degree of Substitution

Abstract: A great number of biologically active compounds contain at least one amine function. Appropriate selectivity can only be accomplished in a few cases upon the substitution of these groups, thus functionalization of amines generally results in a mixture of them. The separation of these derivatives with very similar characteristics can only be performed on a preparative scale or by applying pre-optimized HPLC methods. A tris(pyridino)-crown ether was designed and synthetized for overcoming these limitations at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Therefore, the development of efficient, general, convenient and environment‐friendly protocols for the synthesis of polyfluoro di ‐, tri ‐ and tetra ‐arylmethanes is still a highly desired task so far. In view of the fact that benzyl chlorides is one of the most superior coupling partner, which have the advantages of cheap and easily synthesized by chlorination of benzyl alcohols with some common chlorine reagents SOCl 2 , [22] AcCl, [23] HCl, [24] and CCl 4 , [25] and others. Herein, we reported a transition‐metal‐free direct cross‐coupling of benzyl chlorides with polyfluoro arenes in the presence of magnesium turnings, providing expedited access to a series of polyfluoro di ‐, tri ‐ and tetra ‐arylmethanes (Scheme 1e).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of efficient, general, convenient and environment‐friendly protocols for the synthesis of polyfluoro di ‐, tri ‐ and tetra ‐arylmethanes is still a highly desired task so far. In view of the fact that benzyl chlorides is one of the most superior coupling partner, which have the advantages of cheap and easily synthesized by chlorination of benzyl alcohols with some common chlorine reagents SOCl 2 , [22] AcCl, [23] HCl, [24] and CCl 4 , [25] and others. Herein, we reported a transition‐metal‐free direct cross‐coupling of benzyl chlorides with polyfluoro arenes in the presence of magnesium turnings, providing expedited access to a series of polyfluoro di ‐, tri ‐ and tetra ‐arylmethanes (Scheme 1e).…”
Section: Introductionmentioning
confidence: 99%
“…The polarizable delocalized π-electrons present in the benzene rings of aryl ethers serve as dispersion centers, and the flat nature of the ring allows the formation of nonconventional hydrogen bonding through π-coordination. Recently, crown ether has been used in the separation of amines by HPLC method, and in their study, they identified cation−π interactions and π–π interactions . Kus et al analyzed porphyrin derivative crystal packing and suggested the absence of classical hydrogen bonds between neighbor molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, crown ether has been used in the separation of amines by HPLC method, and in their study, they identified cation−π interactions and π−π interactions. 31 Kus et al analyzed porphyrin derivative crystal packing and suggested the absence of classical hydrogen bonds between neighbor molecules. X-ray studies showed weak contact of C−H•••π in all benzyl units of the porphyrin derivative that forms a network of porphyrin rings by the phenyl or porphyrinyl units.…”
Section: Introductionmentioning
confidence: 99%